2020
DOI: 10.3390/cells9081804
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Accumulation of LAP1:TRF2 Complex during DNA Damage Response Uncovers a Novel Role for LAP1

Abstract: Lamina-associated polypeptide 1 (LAP1) is a nuclear envelope (NE) protein whose function remains poorly characterized. In a recent LAP1 protein interactome study, a putative regulatory role in the DNA damage response (DDR) has emerged and telomeric repeat-binding factor 2 (TRF2), a protein intimately associated with this signaling pathway, was among the list of LAP1 interactors. To gain insights into LAP1′s physiological properties, the interaction with TRF2 in human cells exposed to DNA-damaging agents was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…For FTIR spectroscopy analysis, a fibroblasts density of 0.9 × 10 6 was used. Briefly, primary fibroblasts were cultured and after reaching around 90% of confluency (T75 flasks), the fibroblasts were PBS washed, trypsinazed using 0.05% trypsin-EDTA (Gibco solution and then resuspended in 3 mL of fresh complete medium and cell density determined as previously described [ 31 , 32 ]. A total of 0.9 × 10 6 fibroblasts were used for each replicate.…”
Section: Methodsmentioning
confidence: 99%
“…For FTIR spectroscopy analysis, a fibroblasts density of 0.9 × 10 6 was used. Briefly, primary fibroblasts were cultured and after reaching around 90% of confluency (T75 flasks), the fibroblasts were PBS washed, trypsinazed using 0.05% trypsin-EDTA (Gibco solution and then resuspended in 3 mL of fresh complete medium and cell density determined as previously described [ 31 , 32 ]. A total of 0.9 × 10 6 fibroblasts were used for each replicate.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between DNA damage response and NE is complex, and it is known that several NE proteins play important functions during DNA damage repair, such as the proteins from the LINC complex [ 122 , 123 ] or the Lamin-Associated Protein 1 (LAP1) [ 124 ]. Then, the disruption of NE integrity also compromises the proper DNA repair.…”
Section: Chromosomal Instability Associated To Nedmentioning
confidence: 99%
“…Another study had found that TRF2 transiently formed a complex with laminaassociated polypeptide 1 (LAP1) upon DNA break induction and the complex was recruited at the DNA damage site [141]. Further investigation is needed in order to address the mechanism of TRF2 recruitment to the DSB site and to explore the function of TRF2 in the repair of non-telomeric DNA DSB.…”
Section: Trf2 Involvement In the Ddr Outside Of The Telomeresmentioning
confidence: 99%